PERLINDUNGAN HUKUM TERHADAP ANAK SEBAGAI PELAKU TINDAK PIDANA YANG IDENTITASNYA DI PUBLIKASIKAN - Candrs, Vernanda Ari (Universitas 17 Agustus 1945 Samarinda, 2025)
ABSTRACTThis research aims to determine the legal protection for children as perpetrators of criminal acts whose identities are made public, explaining that legal regulations regarding children's identities that are distributed via social media are formally contained in Article 19 of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, children's identities. Both as perpetrators of criminal acts must be kept secret on social media. In material law, the regulations regarding children's identities distributed via social media are also contained in Article 64 letter i of Law Number 35 of 2014 and Article 26 paragraph (1) of the ITE Law. Other regulations are also contained in the journalistic code of ethics regulations, as guidelines and references for Indonesian press institutions and journalists. This research uses the Normative method. Data sources consist of secondary data consisting of books, journals, laws and regulations related to research problems, data collection techniques are carried out by conducting document studies which are information data, scientific writing. This research uses a problem formulation: How is legal protection for children as perpetrators of criminal acts whose identities are published and the factors that hinder legal protection for children as perpetrators of criminal acts so that their identities are published. What resulted in this research is that a form of legal protection for the identity of children as perpetrators of criminal acts is by understanding and implementing the Juvenile Criminal Justice System Act, namely prioritizing the principles in the Juvenile Criminal Justice System Act and fulfilling children's rights in the criminal justice process. , as well as the role of related institutions. Furthermore, the form of legal protection for children whose identities are spread on social media is to prioritize children's rights to obtain legal assistance, xi xi defend themselves and obtain justice before the court. Perceptions of responsibility and accountability, limited privacy protections in the digital era, and cultural and legal differences between countries also play a role in this issue. To overcome this, joint efforts are needed between legal institutions, the media and society to strengthen existing legal protections, increase awareness of the importance of children's privacy, and promote a more humane approach in handling children's cases in the justice system. The law against children as perpetrators of criminal offenses and the need to maintain their privacy is an integral part of efforts to ensure justice, rehabilitation and well-being for children involved in the justice system. Keywords: Legal Protection, Child Crime, Publication